Do Brahma ao Buda: divergências substanciais entre Hinduísmo e Budismo = From Brahma to Buddha: substantial divergences between Hinduism and Buddhism - Usarski, Frank (Horizonte, 2024)
Hinduism and Buddhism are two of the most significant religions in the world by number of adherents. They also originate from the same region, the Indian subcontinent. In addition, especially in the initial stages of Buddhism, they share a series of theological and symbolic elements. Even so, they have constituted themselves as religious systems of their own, with their own dynamics, which, in many respects, do not mix and are even oppose each other. This article seeks to examine the substantial divergences between Hinduism and Buddhism. To this end, it proposes a circular path, which starts from the similarities between both religions beyond the commonplace, and then deal with the substantial differences.